A Steady MHD Boundary-Layer Flow of Water-Based Nanofluids over a Moving Permeable Flat Plate - Haile, Eshetu; Shankar, B (International Journal of Mathematical Research, 2014)
A steady boundary-layer flow of water based nanofluids over a moving permeable surface were analyzed. The plate was assumed to move in the same or opposite direction to the free stream. The model describing the flow regime characterizes the Sakiadis and Blasius flow scenarios. The PDEs in the governing equations were transformed into ODEs with the help of similarity transformations. The transformed equations were solved numerically by the shooting method with Runge-Kutta integration scheme. Effects of the governing parameters were thoroughly studied and explicitly explained graphically and in tabular form. Numerical results of the velocity field, temperature distribution, skin friction and Nusselt number were obtained. The results were compared with previous works and they are found in excellent agreement.